Aminas bioativas livres e conjugadas no café solúvel: metodologia de análise e influência do processamento. - Tania Maria Leite da Silveira (2008)
Free and conjugated bioactive amines in instant coffee: the methodology of analysis and the influence of processing - The profile and levels of free bioactive amines in instant coffee, as well as the influence of the processing on the levels of free and conjugated amines, were investigates. The method for analysis of free and conjugated amines in coffee beans was optimized, and the post-column derivatizationand fluorimetric detection for the analysis of free bioactive amines by ion pair HPLC was validated. The profile and levels of the free bioactive amines, pH and color characteristics of regular, decaffeinated and regular organic coffee samples commercialized in Belo Horizonte, MG, were analyzed. Ten amines (putrescine, cadaverine, tyramine, histamine, serotonin, agmatine, spermidine, spermine, phenylethylamine and tryptamine) were determined. The total levels of amines in instant coffee ranged from 0.28 to 2.76 mg/100 g. Of the ten amines, putrescine,cadaverine, tyramine, histamine, serotonin, agmatine, spermidine, spermine and phenilethilamine were detected. The tyramine and cadaverine levels were significantly different (p < 0.05) among the three types of instant coffee analyzed. The use of 5% (m/v) trichloroacetic acid with three successive extractions was the best procedure for extraction of free bioactive amines. The hydrolysis of the conjugated amines for theliberation of the free form should be executed with 9 mol/L HCl at 110 ºC for 18 hours. The processing method influenced the profile and the levels of free and conjugated bioactive amines in instant coffee. Roasting decreased the levels of amines so that putrescine, tyramine, spermidine, spermine and tryptamine were not detected in roastedcoffee. The serotonin levels were reduced during the roasting of the coffee. Agmatin formation was observed in the roasted coffee. The total levels of amines increased in the process of concentrating the coffee extract. The acid-soluble conjugated amines were detected in green coffee, and low levels were found in roasted coffee. The acidinsolubleconjugated amines were only detected in green coffee.Key Words: instant coffee, decaffeinated coffee, organic coffee, free bioactive amines, conjugated bioactive amines.